Loyalty in the time of COVID-19: A review of the literature in tourism destination settings - Oliver Cruz-Milán (Frontiers in Psychology, 2023)
Tourism destinations constitute a conglomerate of attractions, service providers, and retailers that make up the overall offerings and experiences that attract visitors. However, given the severe consequences that the COVID-19 pandemic has had on the tourism industry, it is crucial to appraise consumer loyalty towards destinations in the context of the coronavirus disruptions. An increasing number of academic works examining the factors that influence destination loyalty have been carried out since the pandemic breakout, but no evaluation of their cumulative results and findings has been offered in the literature. Therefore, this research conducts a review of studies that have empirically investigated the drivers of destination loyalty during the pandemic in diverse geographical settings. By analyzing 24 journal articles selected from the Web of Science (WoS) database, this work adds to the literature by providing an assessment of the state-of-the-art body of knowledge about the explanation and prediction of loyalty for tourism destinations in the context of COVID-19.